Ecosystem Services of Urban Tree Canopy for the Mitigation of Climate Change: Measuring Carbon Sequestration and Understory Temperature Reduction of Knoxville’s Urban Forest - Tyler Hounshell (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2020)
In the future, the city of Knoxville, Tennessee will be impacted by climate warming due to anthropogenic climate change. Yet, the ecosystem services provided by urban tree canopy in Knoxville’s urban forest can help mitigate the effects of climate warming. In addition to improving air quality, regulating water flow, and reducing noise pollution, Knoxville’s urban forest serves as a carbon sink and sequesters carbon dioxide on an annual basis. Utilizing methods for calculating carbon sequestration by trees in urban and suburban settings developed by the U.S. Energy Information Administration, the sequestration potential and its uncertainty is calculated until the year 2050 for each individual tree. Present sequestration offsets about 1.24% of city-wide emissions, but offset potential more than doubles by 2050 with the urban forest estimated to offset about 2.94% of city-wide emissions. In addition to sequestration benefits, urban tree canopy lowers surface and air temperatures by providing shade and evaporative cooling as two additional ecosystem services. This reduction mitigates rising ambient air temperature for species inhabiting the understory and can be compared to species’ physiological sensitivities in order to estimate population responses to future climate warming. Mapping canopy cover also illustrates where wildlife corridors exist and areas where they need to be developed in order to maintain exchanges between populations fragmented by urban infrastructure. LiDAR data collected in 2016 is processed in GIS software to determine canopy density in Knoxville’s urban forest and other forest land within the city. A case study highlights one application of the canopy cover layer to determine areas of thermal refuge for an understory species, Tamias striatus (the eastern chipmunk). For both high-emissions and low-emissions scenarios, Tamias striatus is not affected by climate warming through 2025, but after that year, areas of refuge beneath canopy cover become critical for maintaining biological fitness.
Keywords: Ecosystem Services; Urban Forestry; Climate Change Mitigation; Geographic Information Science; Sustainable Cities